Inflammation Disturbed the Tryptophan Catabolites in Hippocampus of Post-operative Fatigue Syndrome Rats via Indoleamine 2,3-Dioxygenas Enzyme and the Improvement Effect of Ginsenoside Rb1 - Liu, Shu; Cheng, Yue; Chen, Wei-Zhe; Lv, Jin-Xiao; Zheng, Bei-Shi; Huang, Dong-Dong; Xia, Xu-Fen; Yu, Zhen (Frontiers in Neuroscience, 2021)
Aim: Postoperative fatigue syndrome (POFS) is a common complication which prolonged the recovery to normal function and activity after surgery. The aim of the present study was to explore the mechanism of central fatigue in POFS and the anti-fatigue effect of ginsenoside Rb1. Method: We investigated the association between inflammation, indoleamine 2, 3-dioxygenase (IDO) enzyme and tryptophan metabolism in hippocampus of POFS rats. POFS model of rat was induced by major small intestinal resection. Rats with major small intestinal resection were administrated with ginsenoside Rb1 (15 mg/kg) once a day from 3 days before surgery to the day of sacrifice, or with saline as corresponding controls. The fatigue was assessed with open field test and sucrose preference test. ELISA, RT-PCR, western blot, immunofluorescence and High-performance liquid chromatography were used to test inflammatory cytokines; p38MAPK, NF-κB/p65 and IDO enzyme expression; concentration of tryptophan, kynurenine and serotonin respectively. Result: Our results showed that POFS was associated with an increase expression of inflammatory cytokines, p38MAPK, a higher concentration of kynurenine, tryptophan on postoperative day 1 and 3; a lower serotonin level on postoperative day 1 and an enhanced translocation of NF-κB/p65 and IDO enzyme on postoperative day 1, 3 and 5. Ginsenoside Rb1 had an improvement effect on these. Conclusion: Inflammatory cytokines induced by large abdominal surgery disturb tryptophan metabolism to cause POFS through activation of p38MAPK-NF-κB/p65-IDO pathway in hippocampus. Ginsenoside Rb1 had an anti-fatigue effect on POFS by reducing inflammation and IDO enzyme.